(untitled) (Modern American Journal of Social Sciences and Humanities, 2026)
This article analyzes the theoretical foundations of communist education and its inextricable link with Soviet cultural policy. The goals and principles of the concept of education, formed on the basis of the ideas of Marxism-Leninism, are highlighted. Special attention is also paid to the issues of combining education with labor, the formation of a communist worldview, and atheistic education. The ideological function of cultural institutions in the Soviet era and their place in the centralized management system are scientifically substantiated.